2016
DOI: 10.3762/bjnano.7.88
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependence of the triplet spin-valve effect in superconductor–ferromagnet–ferromagnet heterostructures

Abstract: Summary Background: In nanoscale layered S/F1/N/F2/AF heterostructures, the generation of a long-range, odd-in-frequency spin-projection one triplet component of superconductivity, arising at non-collinear alignment of the magnetizations of F1 and F2, exhausts the singlet state. This yields the possibility of a global minimum of the superconducting transition temperature T c, i.e., a superconducting triplet spin-valve effect, around mutually perpendicular alignment. Results: The superconducting triplet spin va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 72 publications
(111 reference statements)
0
14
0
1
Order By: Relevance
“…Here we observe the simplest MR curves, most consistent with the two-state theoretical prediction based on mono-domain simulations, as in Figure 1c . Namely, a P state at high field with large R xx (suppressed superconductivity) and an AP state at low fields with small R xx (enhanced superconductivity) [ 4 6 8 10 20 , 32 , 34 35 ]. However, this simple scenario does not explain the appearance of additional maxima between the P and AP states.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we observe the simplest MR curves, most consistent with the two-state theoretical prediction based on mono-domain simulations, as in Figure 1c . Namely, a P state at high field with large R xx (suppressed superconductivity) and an AP state at low fields with small R xx (enhanced superconductivity) [ 4 6 8 10 20 , 32 , 34 35 ]. However, this simple scenario does not explain the appearance of additional maxima between the P and AP states.…”
Section: Resultsmentioning
confidence: 99%
“…To facilitate this, we use dissimilar Co layers with thicknesses of 1.5 and 2.5 nm. Nb/Co MLs with similar Co thicknesses have been studied earlier and demonstrated good uniformity and perspectives for device applications [ 25 26 28 , 32 33 43 44 ]. Figure 1b shows a magnetization curve for a similar Nb(25 nm)/[Co(1.5 nm)/Nb(8 nm)/Co(2.5 nm)/Nb(8 nm)] 6 Co(1.5 nm)/Nb(25 nm) unpatterned ML film, deposited using the same setup (data from [ 43 ]).…”
Section: Samplesmentioning
confidence: 99%
“…The exchange bias (EB) effect arises on the interface of antiferromagnetic (AF) and ferromagnetic (F) magnetic phases and leads to the shift of the hysteresis loop on value of H eb varying from several Oersteds to kOe (see review [1]). The effect was discovered 60 years ago, wellstudied to the date [1,2] and is utilized in creation of spin-valves including superconducting devices [3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent calculations have shown [42] that not only the "direct switching" ( ) [42], which can be most spectacularly detected as a reentrant behavior of superconductivity as a function of the angle between magnetic moments of the F1 and F2 ferromagnetic layers. It has been shown that superconducting T c for the F1/N/F2/S structure, calculated with physical parameters derived from the experiments described above, keeps all features predicted in [42] for the simplified model, and the triplet component was detected in F1/N/F2/S multilayer structure [44][45][46][47][48] opening the perspectives for the triplet spin-valve design for superconducting electronics [49,50]. One can see that the functionality of the superconductor/ferromagnet layered nanostructures can be successfully utilized to build a novel base elements for superconducting electronics development.…”
Section: Other Possible Design Of Superconducting Spin Valve -"Triplementioning
confidence: 99%